[PP.16.19] REPRODUCIBILITY OF MORNING BLOOD PRESSURE SURGE IN NORMOTENSIVE AND ESSENTIAL HYPERTENSIVE SUBJECTS. (September 2017) - Lykka, A.; Manousopoulos, K.; Michas, F.; Koroboki, E.; Papageorgiou, C.; Zakopoulos, N.; Manios, E.
Abstract : Objective: Several studies have demonstrated that an exaggerated morning blood pressure surge may be associated with stroke and other cardiovascular events. However, the prognostic value of MBPS for cardiovascular disease has been questioned. One possible cause of this disagreement may concerns the reproducibility of MBPS. Aim of our study was to investigate the reproducibility of MBPS in normotensives and essential hypertensive patients. Design and method: A total of 68 consecutive never treated individuals referred for evaluation at the Hypertension Unit of our department, underwent 24-h ambulatory blood pressure (BP) monitoring at baseline and 1 month. Subjects with 24-h BP values > = 130/80 mmHg were defined as hypertensives, whereas those with 24-h BP <130/80 mmHg as normotensives. MBPS was defined as the sleep-trough surge, calculated by subtracting the morning BP (mean of 4 readings over 2 hours just after wake-up) from the lowest nocturnal BP (mean of 3 readings centered around the lowest nighttime BP) and as the prewaking surge (morning BP minus the 4 readings over 2 hours before waking). Both MBPSs were dichotomized in order to be evaluated as categorical variables as well. Statistical analysis was performed by means of reliability analysis (intraclass correlation coefficient (ICC)) for continuous variables and kappa agreement coefficient for categorical variables. Results: Our study population consisted of 22 normotensive (32%) and 46 hypertensive (68%) subjects. In normotensive subjects the ICC for sleep-trough surge was 0.559 (p = 0.032) and for prewaking surge was 0.655 (p = 0.008). In hypertensive patients the ICCs for sleep-trough and prewaking surge were 0.331 (p = 0.089) and 0.164 (p = 0.273), respectively. When MBPS was dichotomized in low MBPS group and high MBPS group the kappa agreement coefficient for sleep-trough surge was 0.455 (p = 0.033) and for prewaking surge was 0.273 (p = 0.201) in normotensive subjects. In hypertensive patients the kappa agreement coefficient for sleep-trough surge was 0.217 (p = 0.140) and for prewaking surge was 0.043 (p = 0.768). Conclusions: MPBS, by both definitions, is a reproducible phenomenon in normotensive subjects; however, the reproducibility of MBPS in hypertensive patients is very limited.